Use of Generative Artificial Intelligence among Medical Doctors in Sarawak: An Application of the Theory of Planned Behaviour - Siaw Hui, Wong; Noorzilawati, Sahak; Md Mizanur, Rahman (Malaysian Public Health Physicians’Association, 2025)
Generative Artificial Intelligence (GenAI) is emerging as a transformative tool in Malaysia's healthcare sector, with applications ranging from diagnostics to patient care optimisation. Applying the Theory of Planned Behaviour (TPB) to analyse its adoption among medical doctors reveals key drivers and barriers. Data was collected using purposive sampling among 306 medical doctors in primary healthcare settings across Sarawak, using self-administered questionnaire. Structural Equation Modelling (SEM) based on TPB revealed that attitude and perceived behavioural control (PBC) significantly predicted intention to use GenAI, while both intention and PBC had direct effect on actual use of GenAI.